The Influence of Tourist Attractions, Destination Image, and Facilities on Visiting Decisions at the Great Mosque of Central Java Mediated by Electronic Word of Mouth - Azis Syafrudin; Qristin Violinda; Rauly Sijabat (Yayasan Al Ma'arif Dawuhan, 2025)
This research investigates the impact of tourist attractions, destination image, and facilities on visiting decisions at the Great Mosque of Central Java, with electronic word of mouth (eWOM) serving as a mediating variable. The study employs a quantitative approach, using questionnaires distributed to 100 respondents to collect data. The findings reveal that tourist attractions have a significant effect on visiting decisions, indicating that attractive features of the site strongly influence people's choices to visit. However, the destination image does not significantly affect visit decisions, suggesting that the public perception of the overall location may not play a crucial role in influencing visits. Similarly, facilities do not have a significant impact on visit decisions, indicating that infrastructure and amenities alone are not decisive factors for tourists. eWOM is found to significantly influence visit decisions, suggesting that online reviews and recommendations strongly affect tourists' decisions. Additionally, tourist attractions are found to significantly influence eWOM, meaning that the attractiveness of the location encourages online discussions and recommendations. On the other hand, destination image does not significantly affect eWOM, indicating that general perceptions of the destination do not directly influence online word of mouth. Facilities, however, have a significant impact on eWOM, highlighting the importance of amenities in generating online discussions. eWOM is shown to mediate the relationship between tourist attractions and visiting decisions, as well as between facilities and visit decisions. However, eWOM does not mediate the effect of destination image on visit decisions.